Pengetahuan Pelajar Tentang Nilai-Nilai Pancasila Untuk Mempertahankan Ideologi Negara - Galuh Fazry Yanuar; Maulia Depriya Kembara; Rodihati Rodihati; Sabrina Alfarissy Nur Hakim (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
Pancasila as the state ideology is a role model for the Indonesian people in carrying out the life of the nation and state. The purpose of this writing is to find out how far the knowledge of Pancasila values ​​and views on Pancasila values ​​are. The method used is a qualitative approach. From this research it results that the views or opinions given can be concluded that Pancasila is very important as the goal of life for the nation and state. Pancasila is also the goal of the nation's life which is a guide for the good and bad of life in the present.